Суспільно-політичні процеси на території Західної Волині в період української революції 1917-1921 рр. - Крамар, Юрій Вікторович; Kramar, Yurii V. (Житомирський державний університет імені Івана Франка, 2010)
Стаття висвітлює суспільно-політичні процеси, що відбувались на території Західної Волині в період Української революції 1917-1921 рр. Висвітлюється діяльність органів державної влади та управління в регіоні, їх стосунки з центральними органами влади, ставлення місцевого населення до політичних подій, що відбувались в краї.

This article is about the social and political processes in the Western Volyn region during the Ukrainian revolution of 1917-1921. We focus on functionning of the regional administration and on its interaction with the central state government. We also analyse the reaction of the local population as to the political processes taking place in the region.
Social and political processes in Western Volyn during the Ukrainian revolution of 1917-1921.
Keywords: політичне життя; politics; місцеве самоврядування; regional administration; революція; revolution; політична партія; political party